The Effect Of Baby Massage On The Weight Of Babies Aged 3-6 Months In The TPMB Of The Kelapa Gading Region, North Jakarta - Siauta, Jenny Anna; Resi Yesika (International Journal of Midwifery and Health Sciences, 2024)
Regular monitoring of children's growth and development must start from an early age as an effort to obtain quality human resources. Baby massage can reduce morbidity rates, baby massage is useful for increasing baby weight, increasing growth, increasing endurance, increasing breast milk production, improving blood circulation and breathing and improving sleep quality. Baby massage can also optimize baby growth and development. The aim of the research was to determine the effect of baby massage on the weight of babies aged 3-6 months in the TPMB Kelapa Gading area, North Jakarta. This research uses a Quasi Experimental method with a pretest and posttest research design. The sample in this study was 20 babies aged 3-6 months. The sampling technique uses purposive sampling. Data analysis used General Linear Model (GLM) Repeated Measures design with Pretest-Posttest Design. The type of contrast used is difference contrast. During the first week of massage, the average baby's weight increased by 102.5 grams. And by the fourth week, the average baby's weight increased to 297 grams. Overall, the average increase in baby weight was 780.5 grams, this proves that baby massage has proven effective in increasing baby weight. It was found that there was a difference in the average weight of babies before and after baby massage of 780.5 grams at TPMB in the Ranting Kelapa Gading area, Jakarta.